Characteristics Associated With Self-Reported Worry Among Adults About Food Availability and Food Safety During the COVID-19 Pandemic — United States, June 2020. (7th June 2021) - Dumas, Brianna; Lee, Seung Hee; Harris, Diane; Pomeroy, Mary; Yaroch, Amy; Blanck, Heidi
Abstract: Objectives: During the COVID-19 pandemic, U.S. retailers have reported few major, sustained disruptions in food availability (FA); the risk of contracting COVID-19 from eating or handling food is low. Some consumer food behaviors related to FA and food safety (FS), such as panic buying, stockpiling, bleaching food have occurred. During emergencies, assessing consumer nutrition beliefs and developing intervention can prevent unintended negative behaviors. We examined self-reported worry about FA and FS during the pandemic. Methods: Survey data was collected online in June 2020 from a representative panel of US adults (n = 4, 053). Outcome variables (worry about FA and FS) were assessed using collapsed response options ('Worried at any level' and 'Not at all worried) to the question, "How worried are you and your household about each of the following as it relates to the COVID-19 pandemic?" Multivariable logistic regression analyses were used to estimate adjusted odds ratios (aORs) for the associations between sociodemographic variables and worry about FA and FS. Results: Over half of respondents reported worry about FA (58.3%) or FS (57.5%). The highest reported worry about FA were among those not employed (74%), those with household income ≤34, 999 (70%), Black adults (68%), adults aged 35–49 years (64%), those with a high school education or less (62%), and those in the South (61%). The highest reported worry about FS was among those not employed (78%), Black adults (73%), household income ≤34, 999 (74%), aged 35–49 years (61%), and those in the Northeast (61%). Compared with their respective referent groups, significantly higher worry for FA and FS respectively were found among lower income households (aOR [CI] = 1.76 [1.30–2.39]; 1.84 [1.35–2.51]), those who were unemployed (1.54 [1.05–2.28]; 1.90 [1.26–2.81]), non-Hispanic Black (1.55 [1.14–2.12]; 2.25 [1.65–3.07]), and Hispanic (1.39 [1.06–1.82]; 1.94 [1.46–2.56]). Conclusions: Findings highlight the importance of strategies and communications that reduce fears and prevent unintended negative behaviors, and stress increasing consumer awareness of food access options during emergencies, including promotion of hunger safety net programs, especially among disproportionately affected groups. Funding Sources: Solely for author's time from their institutions.